Inventory of greenhouse gases: Central District of Puntarenas (Costa Rica) - Porras-Rozas, Ariel (2020)
In 2018, MINAE (Ministry of Environment and Energy of Costa Rica) made official the Carbon Neutrality Country Program 2.0, for the National Climate Change Strategy. In Puntarenas Central District, UTN leads the efforts for the elaboration of emissions inventories. To get the required information, information requests were sent to key actors in the district and then a poll was applied to the residential, commercial and industrial sector. Emission factors and global warming potential from the IMN was used. The results are the following: in 2016 were emitted 83618.27 ton CO2e, in 2017 were emitted 79053.66 ton CO2e, the greatest contribution is represented by the fossil fuels used in the fishing activity and the transport.